Struktur Biaya dan Efisiensi Usaha Perikanan Tangkap di Kota Bengkulu: Kasus pada Alat Tangkap Gillnet - Mardianto M; Mustopa Romdhon; Ketut Sukiyono (Universitas Teuku Umar, 2015)
This study is aimed at analyzing the cost structure,and the efficiency level ofcatching fishery industry in the city of Bengkulu. Research was conducted in Pulau Baai in the subdistrict at Kampung Melayu,Bengkulu City where was determined purposively. Samples were selected by stratified random sampling. The 60 samples were divided into two strata based on their fishing vessel size, i.e., 1-5 GT and ≥ 6 GT. Full costing approach was used to analyse cost structure of catching fishesy businesses while R/C ratio was applied to determine the level of business efficiency. The estimation found that a variable cost amounted to 83.22 % of total cost, While fixed cost consisted of 16.78 %. Efficiency fishery business level way 1.24 which means that by spending 1 rupiah fisherman will benefit by Rp. 1.24, this means the fishery business was efficient because R/C ratio was hingher than 1. In term of revenue distribution, there is “bagi hasil” pattern between the owner and fishing vessel crews, i.e., with ratio of 50: 50.